2019
DOI: 10.31055/1851.2372.v54.n4.24162
|View full text |Cite
|
Sign up to set email alerts
|

Estructura morfo-anatómica y salida de dormición física de las semillas de Malvastrum coromandelianum ssp. coromandelianum (Malvaceae)

Abstract: Introducción y objetivos: Uno de los principales problemas para el manejo y uso de muchas especies vegetales es la presencia de semillas con dormición física. En este trabajo estudiamos la presencia de dormición física en mericarpos (unidad de dispersión) y semillas, las estructuras morfo-anatómicas involucradas y los métodos de salida de dormición física en semillas de Malvastrum coromandelianum (Malvaceae). M&M: Se realizaron ensayos de imbibición en mericarpos y en semillas intactas y escarificada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of this method on Astragalus gines-lopezii, Astragalus cicer, Parkia biglobosa, Malvastrum coromandelianum ssp, and Phillyrea angustifolia, as well as legume and vigna species. Germination percentages improved from 20% (controls) to between 73% and 100%, respectively [42][43][44][45][46][47][48]. This method eliminates the chalazal zone by creating spaces or cracks (rupture of the palisade tissues) to increase the permeability of the seed testa.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of this method on Astragalus gines-lopezii, Astragalus cicer, Parkia biglobosa, Malvastrum coromandelianum ssp, and Phillyrea angustifolia, as well as legume and vigna species. Germination percentages improved from 20% (controls) to between 73% and 100%, respectively [42][43][44][45][46][47][48]. This method eliminates the chalazal zone by creating spaces or cracks (rupture of the palisade tissues) to increase the permeability of the seed testa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the scarification of seeds demonstrated that dormancy of A. longifolia and A. mearnsii seeds (Milton and Hall 1981;Holmes 1989) is only physical, so any factor able to break the hard coat without causing damage to the embryo will promote germination in a few days. This is a very common type of dormancy among Leguminosae species, but it is not present in all (Ooi et al 2014;Galíndez et al 2019). Arán et al (2017) demonstrated in seeds of A. melanoxylon soil bank that not all seeds of soil bank respond to fire; there remains a part of dormant seeds that could break dormancy through other mechanisms, such as scarification by friction with soil particles or the expansion and contraction caused by summer temperatures.…”
Section: Discussionmentioning
confidence: 99%